PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL PEKERJA HARIAN LEPAS PT.SAMHANA INDAH AKIBAT PEMUTUSAN HUBUNGAN KERJA MELALUI MEDIASI PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI RIAU - Wilton Amos Panggabean; Maryati Bachtiar; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The Daily laborers that worked at Samhana Indah Ltd, Pekanbaru branch, fromthe first time worked hasn’t the employment contract and this situation very posible tomake the industrial relations disputes. The main problem in this research is how toimplemented the working time for the laborers who work more than 20 days in amonth. This contrary to the article 10 Of Indonesian Government Regulation number25 of 2021 about the temporary contract, outsource, break time and the worktermination. Based on regulation the laborers can not work more than 20 days in amonth and if it still continued in 3 months they should become the parmanent workersby law. Because of the work terminnation, the researcher interested and purpose toget to know the solution of the industrial relations disputes between the two partiesand to get to know what are the obstacles while in the mediation process at the RiauProvince Manpower and Transmigration Office.This research can be classified in juridical research, in another term issociological because the researcher was directly conduct on location in order toprovide a complete and clear picture of this research. This research used thedescriptive qualitative method with primary data sources, secondary sources andtertiary sources while the population and sample are the laboures of Samhana IndahLtd, Pekanbaru branch, Riau Province Manpoer and Transmigration Office andIndonesian Legal Aid Foundation – Pekanbaru Legal Aid Institution (YLBHI-LBHPekanbaru). And the Data collection techniuqes are interviews and literature study.The research result show that the solution of industrial relations disputesbetween Samhana Indah Ltd, Pekanbaru branch and the laborers doe to thetermination of laborers are the first effort was resolve in bipartite manner. Next, bymediation to achieve the win-win solution between Samhana Indah Ltd, Pekanbarubranch and the laborers at the Riau Province Manpower and Transmigration Office,but the mediation process didn’t free from the internal laborers’s obstacles and fromthe external. The obstacles from the internal is the laborers still legally blind, meanslack of understanding of their rights and lack of the coordination. And the otherobstacle is lack of facilities and infrastructure while in the mediation process and theboth parties’s ego that unconciously didn’t want to solve the problems by family way.Keywords: Industrial Relations Dispute Resolution – Daily laborers - Mediation